Behind the scenes with genomics researchers - Mont’Alverne, Renata; Bradford, Lori; Buckmaster, Cheryl; Strickert, Graham; MacLean, Jason; Dupont, Diane (Frontiers in Genetics, 2024)
Although lab-coat genomics scientists are highly skilled and involved in pioneering work, few studies have examined their perceptions on what they do, and how they relate with others in interdisciplinary work. Recognizing that gap, we were curious to talk with scientists about their current work and positionalities related to the use of genomics for bioremediation. Using unstructured open-ended interviews and thematic analysis, we interviewed researchers with diverse genomics-related expertise. Emerging topics were grouped into two broad categories akin to Bronfenbrenner’s nested developmental model: microsystem matters, comprising technical advances, barriers, and localized concerns; and macrosystem matters, exploring wider reflections and the philosophies of genomics and society. At the microsystem level, findings revealed differences of opinion about methodological steps, but there was agreement about the incompleteness of databases and the absence of established reference values. These two problems may not only impact a project’s progress but also the ability to gauge success, affecting budgeting, human resource needs, and overall stress. At the macrosystem level, scientists voiced concerns about how different social groups perceive and accept genomics applications, as those tend to be viewed by lay persons as genetic interventions. Another focus was on how academic publication slows progress because it is orientated toward positive results while gaps in knowledge could be filled by publishing negative results or methodological barriers. This study underscores scientists’ self-awareness within the genomics discipline, acknowledging how their beliefs and biases shape research outcomes. It illuminates critical reflections essential for navigating societal and scientific landscapes in genomics research.